Menyusur Dua Alur Lukisan Jelekong - Danuh Tyas Pradipta (JURNAL RUPA, 2019)
Jelekong is the name of a village which located in Kabupaten Bandung. The name of this village has become widely known because of the paintings made by its residents. The paintings are well known by showing landscape, animals and flowers as the object. Later, through several Jelekong painters, the painting has evolved to another kind of painting that is different from the typical Jelekong painting. The emergence of the other painting, not only raises diversity in thematic and painting techniques but more than that, it shows the differences about how the painting is produced, distributed and appreciated, also how Jelekong painter must act differently. To simplify the identification, the two kinds of paintings will be referred as “traditional” Jelekong painting and “contemporary” Jelekong painting. The emergence of both kinds of paintings, with all its difference, shows one thing that is actually fundamental, and that is: the differences of the artworld. Those artworld differences, substantially caused all the difference about both kinds of Jelekong paintings. This paper aims to elaborate further the differences between both of the paintings that evolved in Jelekong. To elaborate all the difference, this paper focused to the sociology aspect of art which underlies both the two kinds of paintings. Sanento Yuliman’s thesis, Dua Seni Rupa, will become the analytical framework for this paper.